Analizing Traffic Accidents on Pekanbaru-Dumai Toll Road from Road infrastructure Perspective - Zaini, Abdul Kudus; Maulana, Syamsul (International Journal of Multidisciplinary Approach Research and Science, 2024)
The Pekanbaru-Dumai (PERMAI) toll road serves a crucial role as the busiest access route in Riau Province. Due to the high volume of traffic on this toll road, it is suspected that various types of traffic accidents occur. This study analyzed the frequency of traffic accidents, accident rate metrics for black-spot and black-site areas, and the condition of road infrastructure on the Pekanbaru-Dumai toll road. This study employed a qualitative descriptive method and collected data from primary sources through field observations and secondary sources, such as accident reports from the Riau Regional Police Traffic Directorate (Indonesian: Direktorat Lalu Lintas POLDA Riau) covering the period from 2020 to 2022 and average daily traffic volume data from the Toll Road Regulatory Agency (Indonesian: Badan Pengatur Jalan Tol [BPJT]). The accident rate formula for black spots and black sites was applied to identify accident-prone and high-traffic areas on the Pekanbaru-Dumai toll road. The analysis results revealed a total of 30 incidents over the three years. The highest accident rate for black-spot areas was 0.10 at KM 34 and KM 35, while the highest for black-site areas was 0.10 at KM 35. Most incidents occurred during the night until early morning, specifically from 18:01 to 02:00. Passenger cars were the most frequently involved vehicles, with 16 single-vehicle collisions. These accidents resulted in 28 victims, including 7 fatalities, 9 serious injuries, and 12 minor injuries. In terms of travel direction, Line A (Pekanbaru to Dumai) experienced 11 incidents, while Line B (Dumai to Pekanbaru) had 19 incidents. The primary factor contributing to these accidents was human error, typically due to negligence or carelessness. Based on observations of road equipment and traffic management on the Pekanbaru-Dumai toll road, the study suggests improving safety by adding noise barriers following Indonesia’s Minister of Transportation Regulation No. 82/2018, Article 33. Additionally, enhancing overall street lighting is recommended, in alignment with Indonesia’s Minister of Public Works Regulation No. 16/PRT/M/2014 concerning Minimum Service Standards.